Turning Words into Weapons of Peace: A Hermeneutical Analysis of Counter Radicalism Values in Musthofa Bisri’s Poetry - Umar, Sururim Maudluunah; Salik, Mohamad; Kurniawan, Andika (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This article discusses resistance to the discourse of religious radicalism spreading rapidly in Indonesia. The passive attitude of some Muslims towards this issue has the potential to threaten the integrity of the Unitary State of the Republic of Indonesia (NKRI), so a serious response is needed. This research emerged from concerns about this phenomenon and aims to understand the forms of resistance against radical ideology through literary works (sastra), particularly the poems of Musthofa Bisri (Gus Mus). The qualitative descriptive approach is based on a literature review, with sources including documents, manuscripts, audiovisual materials, and other written references. This study employs Jorge J.E. Gracia’s hermeneutic approach. The results indicate that Gus Mus’s poems on Islam, nationalism, and the environment serve as an effective medium in countering radical ideology. Through subtle yet sharp satire and criticism, these poems function as a creative and elegant response and an essential tool in preserving national unity, harmony, and peace within society.